EFFECT OF ALUMINUM DROSS AND RICE HUSK ASH ON THERMAL AND MOULDING PROPERTIES OF SILICA SAND (Nigerian Journal of Technology, 2017)
Moulding properties of foundry sand should be controlled so as to minimize casting defects. Its thermal characteristics are vital in defining the solidification kinetics of a cast part,  evolving microstructure and mechanical properties. Modification of the thermal properties of the moulding sand mix is important in achieving desired structure and mechanical properties in the cast component. This study investigates the incorporation of 2-12 wt. % aluminium dross (AlDr) and 1-6 wt. % rice husk ash (RHA) in silica sand on moulding and thermal properties of the resulting sand mix. Results show that RHA significantly reduced thermal conductivity of the moulding sand from 1.631-1.141 W/m. K (a 30% reduction).However, AlDr increased its thermal conductivity from 1.631-1.787 W/m.K for 1-6 wt. % AlDr, which later dropped progressively from 1.753-1.540 W/m.K for 8-12 wt. %. The moisture content increased abruptly from 4.0-4.2 % for 6-8 wt. % AlDr addition but decreased from 4.0-2.8% for0-6 wt. % RHA addition in the moulding sand mix. http://dx.doi.org/10.4314/njt.v36i3.19